Strengthening Pela-Gandong Alliance Based on John Rawls’ Theory of Justice - Juanrico A.S. Titahelu; Irwansyah Irwansyah; Hamid Awaludin; Muhammad Ashri (Faculty of Law, Hasanuddin University, 2015)
Pela-Gandong could be seen as an alliance among two or more villages in Central Maluku territory. Pela-Gandong, besides as brotherhood and friendship among them,this alliance also shared common purpose of cooperation and collective security. Conflict in the beginning of 1999 draws up public attention to the effectiveness of the principles which contains in pela-gandong alliance. Important question come forward because of the plurality condition among current Indonesian society. Should pela-gandong principles nowadays, still playing role to develope social, economy and cultural life of Maluku traditional society? The purpose of this writings is to find out the weaknesses of pela-gandong alliance(s). Based on this, it should offers some suggestion how to strengthening the principles of pela-gandong alliance into the state and the social life in Indonesia.